Comparative Analysis of Four Actuarial Cost Methods on Unfunded Actuarial Liability in a Pekanbaru Pension Scheme - Putri Isnaini Cahyaning Baiti; Nasrullah Nasrullah; Annisa Hevita Gustina Kumalasari Saefulloh; Tika Kristin Marbun (UIN Sumatera Utara, 2026)
Unfunded Actuarial Liability (UAL) is an important indicator in assessing the sustainability of a pension fund program, as it reflects the difference between actuarial liabilities and available assets. This study aims to compare the amount of UAL generated by four pension funding methods, namely Accrued Benefit Cost (ABC), Entry Age Normal (EAN), Unit Credit (UC), and Aggregate Cost Method (AGG). A quantitative actuarial valuation is conducted using administrative data from active civil servants of PT. TASPEN (Persero) Pekanbaru Branch Office in 2025 under uniform actuarial assumptions, including the TASPEN mortality table, interest rates, and salary growth rates. A deterministic sensitivity analysis on the discount rate and salary growth rate was conducted to examine the robustness of unfunded actuarial liability estimates. The results show that the ABC, UC, and EAN methods produce identical aggregate UAL values of approximately Rp. 16.841.220.000, - while the Aggregate Cost Method yields a higher UAL of about Rp.22.173.660.000, - due to collective liability recognition. Furthermore, the EAN and AGG methods exhibit relatively more stable contribution patterns over participants’ service periods, whereas the ABC and UC methods are more sensitive to variations in participants’ age and length of service. These findings indicate that the selection of actuarial cost methods has significant practical implications for pension fund management, particularly in terms of funding stability, contribution planning, and long-term sustainability of pension schemes.